Handbook of transport modelling - Hensher, David A., 1947-; Button, Kenneth, 1948- (Emerald, 2007)
Since 2000, there has been an exponential amount of research completed in the field of transport modelling thereby creating a need for an expanded and revised edition of this book. National transport models have taken on the new modelling methods and there have been theoretical and empirical advances in performance measurement. Coverage will include current demand methods, data issues, valuation, cost and performance, and updated traffic models. Supplementary case studies will illustrate how modelling can be applied to the study of the different transport modes and the infrastructures that support them.The second edition of this handbook will continue to be an essential reference for researchers and practitioners in the field. All contributions are by leading experts in their fields and there is extensive cross-referencing of subject matter. This book features expanded coverage on emerging trends and updated case studies. It addresses models for specific applications (i.e., parking, national traffic forecasting, public transport, urban freight movements, and logistics management).
Includes indexes.
Keywords: Transportation -- General.; Business & Economics -- Industries -- Transportation.; Transport industries.; Transportation -- Planning -- Mathematical models.; elektronické knihy; electronic books